INVESTIGATION OF HARDFACING DEPOSITS OBTAINED BY USING SUBMERGED ARC WELDING FLUXES CONTAINING HIGH-CARBON FERROCHROMIUM AND FERROBORON - Kaptanoglu, M.; Eroglu, M. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2023)
Hardfacing deposition processes were carried out using unalloyed S1-EL12 welding wire and submerged arc welding fluxes produced by agglomerated method containing 4-16 wt.% ferrochromium and 2 wt.% ferroboron to achieve wear-resistant of hardfacing deposits on common steel substrates via submerged arc welding. Typical parameters such as slag detachment behaviour, measurements of weld seam widths and heights, microstructural examinations, and hardness and wear tests of hardfacing deposits were characterized. End of the characterization processes, with the increase of chromium, carbon, and boron transition from welding fluxes to hardfacing deposits, the welding seam widths, and heights were determined to increase from 14.12 mm to 15.65 mm and 6.14 mm to 6.50 mm, respectively. Besides; carbide and boro-carbide ratios in the microstructures increased, the hardness values increased from 43 HRC to 61 HRC and the wear losses decreased from 5.79 to 4.43. (10(-7) mm(3) (N m)(-1)).
Keywords: Submerged arc welding; Hardfacing deposit; Carbide; Boro-carbide; Welding flux